Marital quality among female newly-weds in Klang Valley: the influence of marital communication and gender role - Sahrani, Syah Qurratu Aini; Juhari, Rumaya (International Journal of Children, Women, Elderly and Disable People, 2017)
For centuries, factors influencing marital quality have always been the basic theme among researchers and academicians. As early years of marriage is said to be the most crucial time in married life, various internal and external factors have been seriously debated to ensure the quality of the marriage. Extensive studies have highlighted the importance of gender roles and communication in determining marital quality among newly-weds. This research however, highlighted on the impacts of these two variables on marital quality and focuses only on female newly-weds. Data were gathered from 288 Muslim women who have been married less than 2 years at the time of data collection. Self-administered questionnaires which governs “Dyadic Adjustment Scale”, “Gender Role Attitude Scale”, and the communication sub-scale of “The Three Couple Scale PREPARED/ENRICH: Marital Satisfaction, Communication and Conflict Resolution” were used in order to measure marital quality, gender role and marital communication among the respondents. Results from this study indicate that gender role and marital communication were significantly related with marital quality. In addition, marital communication is the strongest predictor of marital quality among the female newly-weds. In sum, effective communication is an essential tool to ensure the success of intimate relationship such as marriage.